Apprenticeships in homelessness: a quantitative study. Issue 3 (October 2015) - Cebulla, Andreas; Goodwin‐Smith, Ian
Abstract : Training and education are acknowledged routes into employment, but they also entail risks of contemporaneous financial loss, and economic and social insecurity. This paper explores the specific risk of homelessness among apprentices and trainees, drawing on a survey conducted in South Australia in 2013. Housing has been largely overlooked by studies of the wellbeing of apprentices and trainees, and by explorations of the drivers of attrition rates that continue to plague Australia's training schemes. The data examined here reveal the high proportion of income that trainees spent on their housing; home moves motivated by the desire to reduce rental or mortgage payments; and a small proportion of learners who experienced periods of homelessness. Closer statistical analysis reveals that apprentices and trainees with past experiences of homelessness were disproportionately likely to be pursuing courses in retail and personal services, or in transport. They were also likely to be receiving Youth Allowance or AUSTUDY payments. We recommend better recording of apprentices' and trainees' housing situations and greater use of administrative data to improve our understanding and reduce the incidence of homelessness among this population.